REINFORCEMENT OF WOODEN SUPPORTS FOR UNDERGROUND COAL MINES THROUGH FINITE ELEMENT ANALYSIS - Muhammad Asad; Rana Sheharyar Abid; Muhammad Bilal Jamil; Raza Ali Nawaz; Abdul Rehman; Daniyal Abbassi; Ahmad Khobaib Dilsoze; Muhammad Jafar; Dr. Muhammad Zaka Emad (Spectrum of Engineering Sciences, 2025)
Timber is one of the oldest construction materials that remained essential in many industries, including underground mining, where its structural performance was crucial under challenging load conditions. This paper assessed the flexural and uniaxial compressive strength of timber beams reinforced with Sika Wrap-230, Plastic Tie, and Iron Wire using ASTM standards and four-point bending tests. The experimental results, when put together with Finite Element Analysis in ANSYS, established how effective these reinforcements can work to enhance deflection behavior and flexural capacity under timber beams, which means much better performance of timber beams at underground mine supports. The experimental and finite element analysis (FEA) results revealed that the flexural rigidity, strength, and ductility of the timber beam were improved by using Sika Wrap-230 along with Sika Dur. Compared to plastic ties and iron wires, bonding performance was important to be optimized to enhance reinforcement performance. It was suggested to optimized the bonding performance of Sika Wrap-230 by using dedicated adhesives for timber to further enhance reinforcement efficiency. Sika Wrap applied to timber beams placed underground enhanced their strength considerably along with durability in underground mines.